Ecosystem Services at Permata Sentul Golf Club in Bogor Regency - Ardhana, Frisma Aulia; Sulistyantara, Bambang; Hermawan, Rachmad (Media Konservasi, 2025)
Golf courses are green open spaces created for golfing recreation with dominant vegetation in the form of grass. In Indonesia, as one form of green open space landscape, golf courses are widely criticized for their development, resulting in fragmentation and loss of wildlife habitat, two significant causes of biodiversity loss. To address the problem, the golf industry is moving towards more sustainable golf course management to support Sustainable Development Goal 13 on climate change. Through this study, Permata Sentul Golf Club (PSGC) in Bogor Regency, Indonesia was selected to be studied and analyzed to determine its ability to maintain and utilize ecosystem services. PSGC was a natural forest ecosystem in a hilly area that has now been converted into golf course because of a land conversion process without much change to the original condition. This golf course consists of 25% tree-covered rough areas and 54% open areas for gameplay. Located in Tangkil Village, a rural area with extensive rice fields, the course occupies 8% of the village's area. The average air humidity at PSGC is 70.3%, with an air temperature of 27.7°C. Trees at PSGC can store 19.83 tons/ha of carbon, which is included in the low category with carbon absorption of 1.33 tons/year/ha. The dominant tree vegetation types on the PSGC golf course are Mimusops elengi, Acacia mangium, and Schefflera actinophylla. Through the presence of the PSGC golf course, its contributions include providing a microclimate and diverse vegetation, which help create a cooler urban environment and serve as a habitat for various wildlife. However, its carbon storage capacity is still relatively low compared to other green open spaces, especially primary forests. Based on the research findings, strategies can be implemented to optimize the ecosystem services provided by the PSGC golf course. These strategies include enhancing collaboration with various stakeholders from governmental and non-governmental organizations and educating both internal and external parties about the importance of working together to support environmentally friendly programs on the golf course.